Berberine: A Promising Treatment for Type 2 Diabetes Mellitus and Its Associated Dementia – A Review - Staszczyk, Izabela; Drabik, Aleksandra; Szczotka, Dominika; Osuch, Dobromiła; Opala, Dominika; Szemplińska, Antonina; Błachnio, Klaudia; Anderska, Agnieszka (Quality in Sport, 2024)
Introduction and objective: Berberine (BBR) is an isoquinoline alkaloid extracted from various plants. It has been utilized for millennia in traditional Chinese and Ayurvedic medicine. A growing body of evidence supports the beneficial effects of BBR in the treatment of type 2 diabetes mellitus (T2DM) and in reducing the risk of developing related complications. The aim of this study is to review the existing knowledge on the efficacy and safety of BBR in the treatment of T2DM and associated dementia, based on the available scientific literature. Material and Methods: A review of the literature available in the PubMed database was conducted using the following search terms: Berberine; Diabetes Mellitus Type 2; Vascular Dementia; Alzheimer Disease. Current knowledge: The pharmacological treatments of both T2DM and AD have been associated with relatively low efficacy, a high financial burden, and numerous complications that significantly impact patients' daily lives. The exact mechanisms of action of berberine remain unclear. Summary: BBR may be an attractive option for the treatment of T2DM and associated dementia, with therapeutic effects similar to oral hypoglycemic agents, promising neuroprotective properties, a reduced risk of adverse reactions and lower cost. Moreover, BBR improves cerebral blood flow and memory in the rat model of AD. Further scientific research is required to determine the long-term outcomes of this treatment.